2016
DOI: 10.3390/ijms17101636
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Understanding Amino Acid Sensing Mechanisms that Regulate mTORC1

Abstract: The mammalian target of rapamycin (mTOR) is the central regulator of mammalian cell growth, and is essential for the formation of two structurally and functionally distinct complexes: mTORC1 and mTORC2. mTORC1 can sense multiple cues such as nutrients, energy status, growth factors and hormones to control cell growth and proliferation, angiogenesis, autophagy, and metabolism. As one of the key environmental stimuli, amino acids (AAs), especially leucine, glutamine and arginine, play a crucial role in mTORC1 ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
67
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 97 publications
5
67
1
Order By: Relevance
“…The TOR signalling pathway is important in regulating cell growth in response to nutrients (Loewith & Hall, ). Increases in dietary arginine have been found to increase signalling of the TOR pathway, leading to increased cell growth (Zheng et al., ). Slimfast is an amino acid transporter that is found within the TOR signalling pathway, which can sense and transport arginine (Boudko et al., ; Colombani et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The TOR signalling pathway is important in regulating cell growth in response to nutrients (Loewith & Hall, ). Increases in dietary arginine have been found to increase signalling of the TOR pathway, leading to increased cell growth (Zheng et al., ). Slimfast is an amino acid transporter that is found within the TOR signalling pathway, which can sense and transport arginine (Boudko et al., ; Colombani et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of the activity of SLC36 family amino acid (PAT) transporters in cell proliferation and cancer has only recently been fully recognized (22). Here, our data suggest that PAT-mediated sarcosine transport is key to 11 C-sarcosine uptake in prostate cancer.…”
Section: Resultsmentioning
confidence: 52%
“…Also, the mere addition of sarcosine to cultured benign prostate epithelial cells induced an invasive phenotype (4). Although the sarcosine metabolism is well-characterized, its metabolic functions in the human body are still poorly understood and are currently under active investigation (5,22).…”
Section: Discussionmentioning
confidence: 99%
“…CAP1 is a biological target of matrix metalloproteinase-9 (MMP-9). 32 Glycogen synthase kinase 3 (GSK3) phosphorylates CAP1 at Ser307 and Ser309 to regulate its association with cofilin and actin. 28 A number of publications have demonstrated that hormone receptors and G protein-coupled receptors (GPCRs) activate MMP-9.…”
Section: Figurementioning
confidence: 99%
“…[29][30][31] Recent research has also revealed that extracellular amino acids can be sensed by plasma membrane receptors, such as GPRC6A and GPCR T1R1/T1R3, and regulate mTOR. 32 Glycogen synthase kinase 3 (GSK3) phosphorylates CAP1 at Ser307 and Ser309 to regulate its association with cofilin and actin. 33 Oestrogen receptors and some GPCRs can promote phosphorylation, and thus, inhibit GSK3.…”
Section: Figurementioning
confidence: 99%